Expectations and challenges towards complying with the occupational safety and health act 1994: practice in KUKUM - Bahari, Azuddin; Ahmad, Razi; Wahab, Faridah (2006)
Occupational Safety and Health (OSH) Act 1994 or Act 514, requires the workers, employers, societies and government to be involved in ensuring a safe and conducive working environment at the work place against risks to safety or health arising out of the activities of persons at work. This Act applies throughout Malaysia to the industries specified below: a. Manufacturing. b. Mining and Quarrying. c. Construction d. Agriculture, Forestry and Fishing e. Utilities – Electricity; Gas; Water; and Sanitary Services f. Transport, Storage and Communications g. Wholesale and Retail Trade h. Hotels and Restaurants i. Finance, Insurance, Real Estate and Business Services j. Public Services and Statutory Authorities This Act does not apply to work on board ships governed by the Merchant Shipping Ordinance 1952, the Merchant Shipping Ordinance 1960 of Sabah or Sarawak or the armed forces. The Act do not particularly state that universities are to abide to the law. Hence are universities required to abide to the OSH Act 1994? This paper will look into the following aspects i.e. the requirement of the law, expectation and challenges, and how in practice KUKUM endeavor to comply with the OSH Act 1994. It is hope through this working paper; KUKUM will be able to share its knowledge with other institution of higher learning in order to provide and ensure a safe and conducive working environment at the work place against risks to safety or health arising out of the activities of persons at work.